Clinician and patient beliefs about diagnostic imaging for low back pain: a systematic qualitative evidence synthesis - Sharma, Sweekriti; Traeger, Adrian C; Reed, Ben; Hamilton, Melanie; O’Connor, Denise A; Hoffmann, Tammy C; Bonner, Carissa; Buchbinder, Rachelle; Maher, Chris G (BMJ open, 2020)
ObjectiveOveruse of diagnostic imaging for patients with low back pain remains common. The underlying beliefs about diagnostic imaging that could drive overuse remain unclear. We synthesised qualitative research that has explored clinician, patient or general public beliefs about diagnostic imaging for low back pain.DesignA qualitative evidence synthesis using a thematic analysis.MethodsWe searched MEDLINE, EMBASE, CINAHL, AMED and PsycINFO from inception to 17 June 2019. Qualitative studies that interviewed clinicians, patients and/or general public exploring beliefs about diagnostic imaging for low back pain were included. Four review authors independently extracted data and organised these according to themes and subthemes. We used the Critical Appraisal Skills Programme tool to critically appraise included studies. To assess confidence in review findings, we used the GRADE-Confidence in the Evidence from Reviews of Qualitative Research method.ResultsWe included 69 qualitative studies with 1747 participants. Key findings included: Patients and clinicians believe diagnostic imaging is an important test to locate the source of low back pain (33 studies, high confidence); patients with chronic low back pain believe pathological findings on diagnostic imaging provide evidence that pain is real (12 studies, moderate confidence); and clinicians ordered diagnostic imaging to reduce the risk of a missed diagnosis that could lead to litigation, and to manage patients’ expectations (12 studies, moderate confidence).ConclusionClinicians and patients can believe that diagnostic imaging is an important tool for locating the source of non-specific low back pain. Patients may underestimate the harms of unnecessary imaging tests. These beliefs could be important targets for intervention.PROSPERO registration numberCRD42017076047.